2000
DOI: 10.1002/(sici)1097-0010(20000515)80:7<880::aid-jsfa646>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

The potential for the improvement of carotenoid levels in foods and the likely systemic effects

Abstract: Carotenoids form one of the most important classes of plant pigments and play a crucial role in defining the quality parameters of fruit and vegetables. Their role in the plant is to act as accessory pigments for light harvesting and in the prevention of photo‐oxidative damage, as well as acting as attractants for pollinators. Their function as antioxidants in the plant shows interesting parallels with their potential role as antioxidants in foods and humans. Carotenoids are products of the isoprenoid biosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
233
1
7

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(246 citation statements)
references
References 218 publications
(286 reference statements)
5
233
1
7
Order By: Relevance
“…Different extraction procedures were used to isolate carotenoids, including simple solvent extraction, lipid phase distribution (Minguez-Mosquera and Garrido-Fernandez 1989), solid-phase extraction (Gutierrez et al 1989), accelerated solvent extraction (Breithaupt 2004), and supercritical-fluid extraction (Gamlieli-Bonshtein et al 2002). Extraction of carotenoids should be performed quickly, avoiding exposure to light, oxygen, high temperature, and prooxidant metals in order to minimize auto-oxidation and isomerization (Van den Berg et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Different extraction procedures were used to isolate carotenoids, including simple solvent extraction, lipid phase distribution (Minguez-Mosquera and Garrido-Fernandez 1989), solid-phase extraction (Gutierrez et al 1989), accelerated solvent extraction (Breithaupt 2004), and supercritical-fluid extraction (Gamlieli-Bonshtein et al 2002). Extraction of carotenoids should be performed quickly, avoiding exposure to light, oxygen, high temperature, and prooxidant metals in order to minimize auto-oxidation and isomerization (Van den Berg et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Carotenoids are natural pigments known for their coloring properties and biological functions ( VAN DEN BERG et al, 2000). They are synthesized by plants, and, therefore, their presence in animals is attributed to the ingestion of food (OLSON; KRINSKY, 1995;YOUNG;LOWE, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Koka and Karadeniz (2008) registered retention of alpha-and beta-carotene content in cold stored carrots, but a decrease by 38 % of the lutein content. Finally, Van den Berg et al (2000) observed a significant reduction (up to 60 %) in carotene concentration during frozen storage. Mild heat treatments, such as steam blanching, can cause an increase of alpha-and beta-carotene content, probably due to an enhanced chemical extractability because of cell wall disruption.…”
Section: Resultsmentioning
confidence: 88%